PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA SWALAYAN INDOMARET KEBUPATEN SINTANG - Avelius Dominggus Sore; Irma Tripurwanti; Anna Marganingsih (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the effect of service quality on customer satisfaction. This research is a quantitative research. The data processing method used in this research was simple linear regression analysis. The population used in this study were all customers who buy  at the Indomaret Supermarkets, Sintang District. The number of samples in this study were 92 respondents, the sampling method used was simple incidental. Data collection techniques used questionnaires and documentation. The results showed that the quality of service had an effect on customer satisfaction at the Indomaret Supermarkets, Sintang District, based on the t test calculation, the tcount was 2.093 > ttable 1.986, thus it could be concluded that Ha was accepted, with a Sig value. 0.000 <0.05. The coefficient of service determination gives a change in customer satisfaction by 54.6% and 45.4% influenced by other variables, namely product quality, emotional, and price.